Oxidative Dna Damage In Leukocytes And Its Association With Metabolic Control In Diabetic Patients With And Without Microalbuminuria - Sim, Sze Kiat (2001)
Type 2 diabetes mellitus is the predominant type of diabetes mellitus and the type likely to go undiagnosed. Oxidative damage was suggested in the development of diabetic microangiopathic and macroangiopathic complications in these patients. Since the long-term complications are the main cause of morbidity and mortality in diabetic patients, a quantitative determination of the level of oxidative stress is a valuable indicator of the degree of the severity of the disease and of the effectiveness of treatment. The main aim of this study is to evaluate the extent of oxidative DNA damage with different severity of microalbuminuria in diabetic patients and its associations with other metabolic controls. The comet assay was adopted to measure the level of oxidative DNA damage in leukocytes. One hundred and twenty seven (127) Type 2 diabetic patients with- and without microalbuminuria were recruited from the Outpatients Department and